Investigation of Failures during Commissioning and Operation in Photovoltaic Power Systems - SAĞLAM, ŞAFAK; ORAL, BÜLENT (My University, 2024)
Considering global warming and environmental problems, the importance of renewable energy sources is increasing day by day. In particular, the effects of wind and solar power, which are variable renewable power sources, on the power system necessitate their evaluation in terms of the reliability of the power system. Photovoltaic panels, which enable the conversion of solar power into electrical power with semiconductors, have started to take an important place in global energy investments today. Photovoltaic power plants increase the demand for this energy source with continuous energy conversion depending on sunshine duration and radiation intensity. Among the renewable energy sources, the most easily utilized energy source, regardless of geographical conditions, is the sun. To prevent the energy production of PV power plants from being interrupted, it is necessary to address and analyze all kinds of faults that will affect power production in order to increase the reliability of the system. Academic studies in this field are generally grouped under two topics: classification of faults or modeling of electrical faults. Based on this, in this study, the problems that occur during the installation and operation of photovoltaic systems are classified, and the relevant faults are modeled and simulated in MATLAB Simulink version 23.2 (R2023b). Thus, a scientific approach to the problems of photovoltaic power plant operating conditions has been gained, which will be the basis for academic studies.
Keywords: Elektrik-Elektronik Mühendisliği; Enerji; Güç Sistemlerinin Analizi; Yenilenebilir Enerji; Mühendislik ve Teknoloji; Electrical and Electronics Engineering; Energy; Power System Analysis; Renewable energy; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; Elektrik ve Elektronik Mühendisliği; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Yakıt Teknolojisi; Enerji Mühendisliği ve Güç Teknolojisi; Enerji (çeşitli); Genel Enerji; Sinyal İşleme; Fizik Bilimleri; Electrical and Electronic Engineering; Renewable Energy, Sustainability and the Environment; Fuel Technology; Energy Engineering and Power Technology; Energy (miscellaneous); General Energy; Signal Processing; Physical Sciences; commissioning; failure; fault classification; open circuit; photovoltaic; short circuit; MATLAB Simulink